Direct cash assistance: is a solution or a new problem of poverty - Achmad, Willya (ARKA INSTITUTE, 2024)
Although BLT has become one of the main instruments in social development policies in various countries, there is still ongoing debate regarding its effectiveness in reducing long-term poverty. This research aims to investigate the effectiveness and impact of direct cash assistance (BLT) as a strategy for overcoming poverty. This research uses a qualitative approach with descriptive methods. The research results show that Direct Cash Assistance (BLT) has an important role in helping meet the basic needs of vulnerable and needy communities. This program provides direct financial support to those who are economically marginalized, such as poor community groups. However, research also highlights several risks associated with implementing BLT, such as over-reliance, lack of oversight, and potential inflation risks. Therefore, research emphasizes the importance of continuous evaluation and improvement in the implementation of the BLT program so that it can provide a more sustainable impact in overcoming poverty and improving the welfare of society as a whole.